2022
DOI: 10.3390/ijms231710072
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of High-Fat Diet-Induced Non-Alcoholic Fatty Liver Disease by Metformin Combined with PGG, an Inducer of Glycine N-Methyltransferase

Abstract: Nonalcoholic fatty liver disease (NAFLD) is a major cause of liver-related morbidities and mortality, and no effective drug treatment currently exists. We aimed to develop a novel treatment strategy to induce the expression of glycine N-methyltransferase (GNMT), which is an important enzyme regulating S-adenosylmethionine metabolism whose expression is downregulated in patients with NAFLD. Because 1,2,3,4,6-pentagalloyl glucose (PGG) is a GNMT inducer, and metformin was shown to upregulate liver mitochondrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 56 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…9 PGG also acts on a variety of bio-targets associated with diabetes, for example, protein tyrosine phosphatase 1B (PTP1B), 10 PPARα, and PPARγ. 11 PGG can also inhibit diabetes development in mice via the 11β-HSD-1 target. 12 In our systematic screening of polyphenols, we also found that PGG can significantly inhibit α-glucosidase in the mixed mode.…”
Section: Introductionmentioning
confidence: 99%
“…9 PGG also acts on a variety of bio-targets associated with diabetes, for example, protein tyrosine phosphatase 1B (PTP1B), 10 PPARα, and PPARγ. 11 PGG can also inhibit diabetes development in mice via the 11β-HSD-1 target. 12 In our systematic screening of polyphenols, we also found that PGG can significantly inhibit α-glucosidase in the mixed mode.…”
Section: Introductionmentioning
confidence: 99%